2021
DOI: 10.1002/app.50642
|View full text |Cite
|
Sign up to set email alerts
|

A high Cr (VI) absorption efficiency and easy recovery adsorbent: Electrospun polyethersulfone/polydopamine nanofibers

Abstract: Cr (VI) is a highly toxic pollutant to humans, to achieve high adsorption capacity, easy recovery, and good reusability, polyethersulfone/polydopamine (PES/PDA) ultrafine fibers were prepared successfully. A series of preparing effect factors were investigated systematically and the optimum one is 8.5 pH value at room temperature and 2 g/L dopamine concentration. And then they were used as an adsorbent for the removal of Cr (VI) ions from wastewater. The effect factors pH, the adsorbent dosage, and time were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Adsorption is considered as the most promising method due to its high efficiency, easy to operate, economical, renewable, and technological feasibility. 20,21 Numerous adsorbents including silica gel, 10,22 various types of nanomaterials, [23][24][25] nanobers, 19,26 biochar, 20,27 hydrogel, 28 functionalized polymers, 8,29 metal composite 30 and metal-organic frameworks 31 have been used for Cr(VI) removal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adsorption is considered as the most promising method due to its high efficiency, easy to operate, economical, renewable, and technological feasibility. 20,21 Numerous adsorbents including silica gel, 10,22 various types of nanomaterials, [23][24][25] nanobers, 19,26 biochar, 20,27 hydrogel, 28 functionalized polymers, 8,29 metal composite 30 and metal-organic frameworks 31 have been used for Cr(VI) removal.…”
Section: Introductionmentioning
confidence: 99%
“…The increased adsorption with temperature indicated that the adsorption was endothermic. 19,25,26,62 It was presumed that the increase in temperature and the acceleration of ion motion lead to the acceleration of electrostatic attraction and reduction reactions. It was consistent with the rate change of a redox reaction with temperature.…”
mentioning
confidence: 99%
“…[12,13] Long-term exposure to hexavalent chromium more than the permissible limit can cause nausea, nervous disorder, kidney failure, liver diseases, and cancer. [14,15] The various technologies developed for Cr (VI) removal from water or wastewater streams include chemical precipitation, [16] ion exchange, [17] bioremediation, [18] photocatalytic reduction, [19] electrokinetic, [20] remediation membrane separation, [7] electrodialysis, [21] and adsorption. [22] Among these, the adsorption method is widely used in the cleaning of Cr (VI) contaminated water due to its wide range of raw materials and no by-products, easy recovery, simple operation, and high efficiency.…”
Section: Introductionmentioning
confidence: 99%